Norwegian "dugnad" as a rhetorical device in public health communication during the COVID-19 pandemic. A qualitative study from immigrant's perspectives - Raquel Herrero-Arias; Irina Vladimirovna Halbostad; Esperanza Diaz (BMC, 2024)
Abstract Background During the COVID-19 pandemic, the Norwegian government appealed to the term "national dugnad" in the communication of containment measures as a call for collective action to fight the spread of infection. "Dugnad" is traditionally associated with solidarity, social responsibility, and a communal spirit in the form of volunteer work carried out by a local community. Although the word "dugnad" is difficult to translate to other languages, it was used as a rhetorical device by the government to communicate health-related information during the pandemic. This study aims to explore how immigrants understood and related to the term "dugnad" as used in the context of the COVID-19 pandemic in Norway. Methods We conducted 55 semi-structured interviews in 2020 with immigrants from Poland (10), Syria (15), Somalia (10), Sri Lanka (10), and Chile (10). Interviews were conducted in participants' mother-tongues. We used systematic text condensation following Malterud's four steps to analyze the data. Results The results are organized into three themes corresponding to: (1) meaning making of the term "dugnad"; (2) attitudes towards the term "dugnad"; and (3) reactions to the use of "dugnad" in a public health context. Overall, participants were familiar with the term "dugnad" and positively associated it with volunteering, unity, and a sense of community. However, we found a variety of reactions towards using this term in a public health context, ranging from agreement to disagreement and irritation. Conclusion Health communication during pandemics is crucial for maximizing compliance and gaining control of disease spread. In multicultural societies, governments and authorities should be aware of the linguistic and cultural barriers to public health communication if they are to effectively reach the entire population. The use of culturally specific concepts in this context, specially as rhetorical devices, may hinder effective health communication and increase health inequalities.